Impact of different sports and training on cardiac structure and function - Fagard, R. H. (Cardiology Clinics, 1997)
There is overwhelming evidence, particularly from echocardiography, that the heart of competitive athletes may differ from that of nonathletes, matched for age, gender, and body size. A larger left ventricular mass has been shown in athletes performing predominantly dynamic aerobic and anaerobic sports, in athletes engaged in static training, and in players of ball sports. Enlargement of the left ventricular internal diameter was most pronounced and reached about 10% in athletes performing predominantly dynamic sports; mainly strength training athletes had a lesser increase of the internal dimension, which was limited to 2.5%. Also the left ventricular wall appeared to be thickened in all types of athletes compared with controls. In sports with high dynamic and low static demands, wall thickness was proportionate or slightly disproportionate to the size of the internal diameter so that relative wall thickness was not different from controls or slightly increased (predominantly eccentric hypertrophy). In strength athletes, the disproportionate increase of wall thickness averaged about 12% (predominantly concentric hypertrophy). In sports with high dynamic and high static demands and requiring prolonged training, such as cycling, the increases of absolute and relative wall thickness reached 29% and 19% and were more pronounced than in runners (mixed hypertrophy). A plausible interpretation of these results is that the development of so-called eccentric or concentric left ventricular hypertrophy according to the type of sports cannot be regarded as an absolute or dichotomous concept because training regimens and sports activities are not exclusively dynamic or static and because the load on the heart is not purely of the volume or the pressure type. Most studies agree that left ventricular systolic and diastolic function is normal in the athlete at rest, whereas diastolic function seems to be enhanced in the exercising endurance athlete. The consistency of the results of studies on athletes in the competitive and the resting season, of training of sedentary subjects, and of spinal cord-injured patients suggests that variations in physical activity can alter left ventricular structure; genetic factors do not seem to be involved in the size of the left ventricular internal diameter but have to be taken into account to interpret wall thickness.